Pelatihan Pembuatan Produk Keripik Melon Menggunakan Alat Dehydrator bagi Kelompok UMKM Inkubator Bisnis Teknologi (ITe) Unizar - Rosadi, Narita Amni; Novida, Sari; Syuhriatin, Syuhriatin; Juniawan, Alvin (Jurnal Pengabdian UNDIKMA, 2023)
This Community Service program aims to increase the knowledge and skills of ITe Universitas Islam Al-Azhar MSME group members in making rock melon chips using a Dehydrator. The training was conducted through several stages: planning, implementation, monitoring, and evaluation. The participants for this service were the university's business technology incubator MSME group consisting of rock melon farmers and chip entrepreneurs, with 35 participants. The activities resulted in the participants' understanding of making rock melon chips using the Dehydrator tool could increase after the training, as well as understanding regarding the packaging of fruit chip products that were durable and long-lasting.